The Play Interaction Programme sebagai Strategi Penguatan School Connectedness pada Siswa Sekolah Dasar - Ridha, A. Ahmad; Kusumawati, Kusumawati; Putri, Monica Hattasyah Apriliana; Wulandari, Della Puspita; Ardianto, Ardianto (Jurnal Psikologi Integratif, 2024)
This research is motivated by the tendency of elementary school students to be reluctant to attend school, avoid academic tasks, and express unhappiness in the school environment. This indicates that students have low school connectedness. Considering the importance of school connectedness in students, this research aims to address the issue of low school connectedness by providing the Play Interaction Program intervention to elementary school students with low school connectedness. The purpose of this study is to overcome the problem of low school connectedness in elementary school students. The hypothesis in this research is that the Play Interaction Program is effective in improving the school connectedness of elementary school students. This research uses a quantitative approach with the experimental research type of one group pre-post-test design. The subjects in this study are 16 students identified as having low school connectedness. The results of the Wilcoxon test show that the Play Interaction Program is effective in improving the school connectedness of elementary school students. School connectedness in students significantly increased after the Play Interaction Program intervention. This research provides an alternative in improving school connectedness by using joyful learning strategies in the teaching and learning process, ensuring that the school connectedness of elementary school students is maintained. Penelitian ini dilatari oleh adanya kecenderungan siswa sekolah dasar yang enggan bersekolah, menghindari tugas-tugas akademik dan menunjukkan perasaan tidak bahagia berada di sekolah. Hal ini mengindikasikan bahwa siswa memiliki school connectedness yang rendah. Mengingat pentingnya school connectedness pada siswa, maka penelitian ini berupaya memecahkan permasalahan school connectedness dengan memberikan intervensi the play interaction programme pada siswa sekolah dasar yang memiliki school connectedness yang rendah. Penelitian ini bertujuan untuk mengatasi permasalahan school connectedness yang rendah pada siswa sekolah dasar. Hipotesis dalam penelitian ini, yaitu the play interaction programme efektif dalam meningkatkan school connectedness siswa sekolah dasar. Penelitian ini menggunakan pendekatan kuantitatif dengan tipe penelitian eksperimental one group pre-post test design. Subjek dalam penelitian ini berjumlah 16 orang siswa yang teridentifikasi memiliki school connectedness yang rendah. Hasil uji wilcoxon menunjukkan bahwa the play interaction programme efektif dalam meningkatkan school connectedness siswa sekolah dasar. School connectedness pada siswa mengalami peningkatan secara signifikan setelah diberikan intervensi the play interaction programme. Penelitian ini memberikan alternatif dalam meningkatkan school connectedness yaitu  dengan menggunakan strategi joyfull learning dalam proses belajar mengajar sehingga school connectedness siswa sekolah dasar tetap terjaga.